Cooperation With Universities in the Development of Eco-Innovations and Firms’ Performance - Arroyave, Juan J.; Sáez-Martínez, Francisco J.; González-Moreno, Ángela (Frontiers in Psychology, 2020)
In recent decades, the expansion of economic activity has been accompanied by negative environmental impacts. In response, there have been dramatic changes worldwide in terms of an increased demand for environmentally friendly products and services. To achieve these eco-innovations, firms have sought to acquire knowledge and implement operational flexibility by cooperating with different agents such as universities through a value cocreation system that is also expected to enhance firms’ performance. Using a sample of 250 companies, the present paper examines the role of cooperation with universities in the development of diverse environmental innovations and building operational flexibility and, through this, improving firm performance. Results show that firms that value cooperation with universities develop a wider range of environmental innovations and increase their sales and benefits.